Understanding driver responses to voice alerts of autonomous car operations. (2016) - Koo, Jeamin; Shin, Dongjun; Steinert, Martin; Leifer, Larry
This study explores, in the context of automated braking, how a voice alert accompanying the car's autonomous action affects the driver's attitude and driving behaviour. To examine the research question we designed an experimental setup in a simulator environment that (1) enabled automatic braking to perform as a vehicle's autonomous longitudinal behaviour and (2) enacted a voice alert system in a timely way to notify the driver of pending brake actions. Subjective driving experience and driver responses towards the car were strongly affected by the voice alerts when the car made automated decisions. These results have important implications for the design of vehicle-user interfaces, suggesting that, rather than simply developing a car that executes autonomous decisions, car makers should also focus on the human-machine interaction, i.e., on how the car announces its 'intentions' to act.